Donated human milk use and subsequent feeding pattern in neonatal units - Wesam Alyahya; Debbie Barnett; Andrew Cooper; Ada L. Garcia; Christine A. Edwards; David Young; Judith H. Simpson (BMC, 2019)
Abstract Background Donated human milk (DHM) is a safe alternative in the absence of mother's own milk (MOM); however, specific clinical indications for DHM use and its impact on subsequent feeding practice remain unclear. We aimed to audit local DHM use and explore the impact of the introduction of DHM as the first enteral feed on subsequent MOM availability. Methods We retrospectively audited DHM recipients nursed in Royal Hospital for Children, Glasgow from 2014 to 2016 against local guidelines. Data were collected from an operational electronic database. Descriptive data analysis was performed to describe DHM use. To explore the association between the first human milk feed with subsequent MOM availability Kruskal Wallis test was used. Adjustments for confounding variables were performed using analysis of variance (ANOVA). Results A total of 165 recipients of DHM (5.3% of all admission to RHC) were identified. The majority of recipients (69%) were born < 32 weeks of gestation. The main indication for DHM was prematurity, other indications included congenital anomalies of bowel and heart. The local guideline was adhered to in 87% of cases. The median interquartile range (IQR) at DHM introduction was 6 days (3, 17) and the duration of use was 12 days (6, 22). In those born < 32 weeks of gestation the type of human milk (DHM and/ or MOM) used as first feed did not influence the subsequent median IQR days of feeding with any MOM [DHM 40 (9, 51); MOM 28 (17, 49), MOM & DHM 17 (10, 26) p value = 0.465] after adjusting for birthweight and length of hospital stay. Conclusions In our unit, DHM is mainly used in preterm neonates in accordance with existing local guidance. Using DHM as first milk feed did not affect subsequent MOM availability.